PENGARUH BERKUMUR DENGAN LARUTAN PROBIOTIK TERHADAP KADAR IgA DALAM SALIVA - Recita Indraswary; Hilma Yunita Nurenda; Helmi Faturrahman (Mandala Of Health, 2021)
ABSTRACT Saliva contains IgA which acted as the first line of defense against a pathogen in the oral cavity. IgA salivary in the elderly have decreased which caused prone to oral infection. The alternative way to increased salivary IgA levels was by gargling a probiotic solution. Gargling was a mechanical stimulation to increase the flow rate of saliva. Probiotic contains bacteria which can give advantage for the human body. Probiotics can stimulate the immune system to increased IgA levels. The purpose of this study was to determine the effect of gargling probiotic solutions on salivary IgA levels in the elderly. This study used a quasi-experimental pre and post-test design group. The number of samples was 11 people. Each sample was instructed to gargling probiotic solution 10 ml every morning and evening along with their saliva was taken before and after gargle the probiotic solution. Data analysis was done using a paired t-test. The result showed the mean of salivary IgA levels before gargling probiotic solution were 206.6818±25.17419 and salivary IgA levels after gargling probiotic solution were 223.4091±12.52042. Based on the paired t-test got a value of p=0.059 (>0.05) means there is no significant difference. The conclusion of this study was gargling probiotic solution can increase salivary IgA but is not statistically significant. Keywords: Salivary IgA, probiotic solution, elderly